Design and evaluation of a secure key exchange protocol using the Kyber-Dilithium algorithm - Bambang Harjito; Muhammad Defaroyan; Fajar Muslim; Ery Permana Yudha; Endra Pratama (Institute of Advanced Engineering and Science, 2026)
Over 90% of the billions of people who use the internet globally use it through the transport layer security (TLS) protocol. TLS is a security standard that performs network authentication and data encryption when accessing the internet. Authenticated key exchange (AKE) is the protocol TLS uses for network authentication and key establishment during the TLS Handshake process. The AKE protocol utilizes a public key cryptosystem (PKC) and digital signatures with algorithms commonly used, namely elliptic curve cryptography (ECC) and Rivest-Shamir-Adleman (RSA). Future advancements in quantum computing may compromise the security of the widely used ECC and RSA algorithms. This research conducts an implementation and comparative analysis of post-quantum algorithms resistant to quantum computer attacks, specifically Kyber-Dilithium, in the context of the AKE protocol. The implementation is performed at three security levels: 128-bit, 192-bit, and 256-bit. The results show that the Kyber-Dilithium is greater than those of the RSA variant and much larger than those of the ECC variant. In contrast to the ECC and RSA variants, the Kyber-Dilithium algorithm variants perform better across all security levels, even if their byte sizes are greater.